Grasshoppers in summer [large type] - Colt, Paul (Wheeler Publishing, a part of Gale, a Cengage Company, 2021)
"On December 21, 1866, Red Cloud and the band of Oglala, Lakota, and Cheyenne warriors defeated a U.S. Army force led by Captain William J. Fetterman. The Fetterman defeat ended Rad Cloud's war for control of the Bozeman Trail with the signing of the Fort Laramie Treaty of 1868. GRASSHOPPERS IN SUMMER tells the epic story of making and breaking the Fort Laramie Treaty as seen through the eyes of opposing political, military, railroad, and mining interests destroyed the Fort Laramie Treaty, leading to the drumbeat of war. The Plains tribes' last great victory at Greasy Grass would win the bitter spoils of total defeat."--Back cover.